MOBILE APPLICATIONS FOR ACCOUNTING AUTOMATION: NEW OPPORTUNITIES FOR ENTREPRENEURS AND ACCOUNTANTS - BRAZILII, Nataliia; CHYCHUZHKO, Maryna; KROT, Yuliia; PASTERNAK, Yaroslava (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to the development of a mobile application designed to automate accounting processes for a sole proprietor. In the modern economic environment, digital tools are becoming an integral part of small business management. The mobile application described in the article aims to streamline routine accounting operations, improve the accuracy of financial data processing, and reduce the time required for record-keeping and reporting. The main functionality of the application includes income and expense tracking, tax reporting, and analytics visualization. The research emphasizes the growing demand for flexible, easy-to-use, and secure financial management tools that can be accessed remotely and updated in real-time. The developed application provides an intuitive interface and integrates with existing cloud storage solutions to ensure data security and accessibility. A comparative analysis was conducted between traditional manual bookkeeping methods and the proposed mobile solution, highlighting the latter’s advantages in terms of operational efficiency, data integrity, and user experience. Special attention is given to the challenges of integrating the application into the existing infrastructure of a sole proprietor’s business. These include synchronization with tax authority requirements, ensuring compliance with local legislation, and scalability to support the growth of the business. The study concludes that the use of mobile technologies in accounting significantly contributes to the digital transformation of microenterprises, helping entrepreneurs make timely decisions based on real-time financial data. The developed solution serves as a practical example of how modern information technologies can be used to optimize business processes, reduce administrative burdens, and enhance financial transparency.